Routine surveillance imaging after end of therapy for pediatric extracranial tumors: A retrospective analysis. Issue 1 (20th July 2017) - Lakkis, Farah; Alaiwi, Sarah Abou; Naffaa, Lena; Atweh, Lamya; Khoury, Nabil; Abboud, Miguel; Muwakkit, Samar; Tarek, Nidale; El Solh, Hassan; Saab, Raya
Abstract: Frequent surveillance imaging is routine practice for pediatric patients after cancer therapy. This retrospective study evaluated the follow‐up of 301 children with extracranial tumors diagnosed between 2002 and 2012, at a tertiary pediatric cancer center in Beirut, Lebanon. Recurrence occurred in 15% of patients, at a median of 12 months after end of primary therapy. Outcome was not different comparing patients with recurrence detected via imaging surveillance versus clinically. False positive findings in 55 patients led to further interventions. These results raise important questions regarding benefit of current surveillance practices as standard care, especially in countries with limited resources.